Formulación de una crema exfoliante a partir de limoneno extraído de residuos de cáscara de naranja (Citrus Sinensis L.) Mediante el método de extracción asistida por ultrasonido. (2025)
This work aims to generate the use of orange peels in a limonene extraction process from them using the ultrasound-assisted extraction method, in order to use it in the formulation of an exfoliating cream. This study proposes a composite central experimental design to evaluate the operating conditions in the extraction of limonene from orange peels using the ultrasound-assisted extraction method. A substrate-solvent ratio of 1:5 was used, using 10g of previously cut and dried orange peels and 50mL of solvent; the samples were subjected to an ultrasound bath (DIGITAL ULTRASONIC CLEANER), the temperature and time values ​​were established according to the experiment to be performed.